The Psychological Well-Being of Young Women Entering into Child Marriages - Nadia Rizkiani; Dian L. Anakaka; Juliana M. Y. Benu (Journal of Health and Behavioral Science, 2023)
The phenomenon of child marriage is a problem that occurs worldwide. Adolescents who engage in child marriage tend not to achieve psychological well-being. This is closely related to emotional maturity in resolving family conflicts. This research uses qualitative methods with a phenomenological approach. The data collection procedure consisted of interviews and documentation for 3 participants with a marital background, as they were engaged out of wedlock and pregnant. The results showed that young women who underwent child marriage did not have good psychological well-being. This is evident in the aspects of self-acceptance, positive relationships with others, autonomy, mastery of the environment, Purpose in life and personal growth. Young women's psychological well-being is also affected by several factors, including support, change, compassion, motivation, counsel, problem solving, and knowledge of marriage. Adolescents who are successful and able to overcome their problems are said to reach a state of psychological well-being, which means that this leads to the state of individuals who are able to face various things that can trigger problems in their lives.